(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article presents information about the preliminary results of the research work carried out to develop optimal irrigation procedures using the method of drip irrigation of soybean varieties, taking into account the growing demand for food in the world and our country, and the increase in the cost of environmentally friendly protein.